Properties and rapid sintering of nanostructured CoAl-Al2O3 composite for prosthetic joint replacements - Lee, Dong-Gu; Yoon, Jin-Kook; Hong, Kyung-Tae; Shon, In-Jin (세라믹공정연구센터, 2016)
Even though Al2O3 material having high hardness reduces wear debris materials, it cannot satisfy the properties of prosthetic hip or knee join replacements because of its low fracture toughness. Thus, bearing materials in prosthetic hip or knee joint replacements basically require high hardness and high fracture toughness. To improve their mechanical properties (hardness and fracture toughness), the approach commonly utilized has been the addition of a second phase to form a composite and produce nanostructured materials. The nanopowders of CoAl and Al2O3 were synthesized from Co3O4 and Al powders by high energy ball milling. The nanostructured 2.25CoAl-Al2O3 composite from the milled powder was densificated within a short time by the high frequency induction heated sintering. The mechanical properties of the nanostructured 2.25CoAl-Al2O3 were higher than those of monolithic CoAl and Al2O3, respectively. And the composite was evaluated as excellent biocompatibility.